Analysis of Heuristic and Hermeneutic Reading in Burdah Book: A Study of Michael Rifaterre's Semiotic Approach - Tamim Mulloh; Habil Abyad; Nurul HIkmah; Ahmad Nilnal Munachifdlil Ula (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2023)
This study aimed to analyze the application of Michael Rifaterre's semiotic approach in discussing heuristic and hermeneutic reading methods in the book of Burdah. This research used a qualitative approach with a focus on text analysis. The method used involves Michael Rifaterre's semiotic approach as the main framework. Data was collected through literature studies related to Burdah and semiotic approaches, as well as analysis of Burdah texts using heuristic and hermeneutic lenses. The results showed that the heuristic approach helps reveal symbolic and metaphorical elements, while the hermeneutic approach deepens the understanding of the historical and cultural context surrounding Burdah. Thus, a combinative reading of both approaches forms a more holistic understanding. The study concluded that Michael Rifaterre's semiotic approach can be an effective framework for analyzing heuristic and hermeneutic readings in classical Islamic texts such as Burdah. The combination of the two approaches enriches the understanding of literary work, revealing deeper layers of meaning.